PENERAPAN NILAI KODE ETIK KEDOKTERAN INDONESIA (KODEKI) PADA ERA JAMINAN KESEHATAN NASIONAL DI KOTA DUMAI - Vani Ardiani; Dedi Afandi; Mohammad Tegar Indrayana (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTImplementation of Indonesian Medical Codes of Ethics (KODEKI) values has been public’s highlight ever since National Health Coverage (NHC) is undergone. This is doctor’s autonomy in serving the patients has been limited. The aim of this research is to see how the implementation of the six values of KODEKI in NHC in Dumai City. This qualitative research was using exploration method towards four selected general practitioners who was chosen by snowball sampling method and thus called as informants. Data was collected by using interview technique and recorded by audio recorder. The result showed that each of the informants have all the six values of KODEKI which compromises of altruism, responsibility, professional idealism, accountability, scientific integrity, and social integrity in Dumai eversince NHC has been implemented. This is proven by the informants’ statements which was validated using triangulation technique.Keywords:KODEKI values, national health coverage, Dumai city.